Environmental information dissemination and preservation in Nigeria (1999)
This paper is largely connected with collecting data on the role of two enviromental agencies, Federal Environmental Protection Agency(FEPA) and the Nigerian Environmental Study/Action Team(NEST) in dissemination of environmental information and to find out how effective these have been on the level of awareness of a selected group pf people. The result of the study indicated that FEPA and NEST used some media of information to pass information on the environment across to the people. however, it was discovered that few people among the information user group have a faint knowledge about the existence of these environmental agencies should invlove information scienctist, educators and librarians in helping them with thier communication skills.